Modely standardů pro podporu rozhodování v managementu veřejné správy - Černá, Anna (Univerzita Pardubice, 1999)
The paper deals with the problem of "objective standards" of public services. E.g. in the regional public transport there exist attempts to define minimum necessary number of bus connection/day for a village using a "macro" model. The paper proposes an other approach of a "micro" type.
Keywords: Management; standardy; modely; veřejná správa